POTRET KONFLIK AGRARIA DI INDONESIA - Widiyanto, Widiyanto (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
For the last three years (2010-2013) the conflicts on natural and agrarian resources has taken public attention beginning from the Government, Parliement, National Commission on Human Right to Non Governmental Organization as they frequently took place. The conflicts, which had been previously latent, later they came into existence.The article talks about the portrait of the agrarian conflicts taking place in Indonesia in general. Keywords: conflicts, agraria, Indonesia, natural resources.